1983
DOI: 10.1073/pnas.80.11.3193
|View full text |Cite
|
Sign up to set email alerts
|

Close relationship between the long terminal repeats of avian leukosis-sarcoma virus and copia-like movable genetic elements of Drosophila.

Abstract: A new species of copia-like movable genetic element termed 17.6 was identified in Drosophila melanogaster, and the nucleotide sequences of its long terminal repeats (LTRs) were determined. The LTRs of 17.6 were not only homologous to those of 297, a sibling movable genetic element of 17.6, but also closely matched those of avian leukosis-sarcoma virus. This made it possible (i) to identify the nucleotide sequences in 17.6 and 297 that correspond to the crucial regulatory sequences for both transcription and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Distribution of copy numbers of transposable elements, P, 297, and copia between lines of Akayu population in D. melanogaster genome since some transposons such as 17.6 and 297 have target-sequencespecificity (Ikenaga and Saigo 1983;Inouye et al 1984) . However, the nonrandomness of the inserted sites is not so conspicuous since more than 105 ( _ 1.6 X 108/44) target sites are expected to be present in a genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of copy numbers of transposable elements, P, 297, and copia between lines of Akayu population in D. melanogaster genome since some transposons such as 17.6 and 297 have target-sequencespecificity (Ikenaga and Saigo 1983;Inouye et al 1984) . However, the nonrandomness of the inserted sites is not so conspicuous since more than 105 ( _ 1.6 X 108/44) target sites are expected to be present in a genome.…”
Section: Resultsmentioning
confidence: 99%
“…Among them are copia, 297 and P elements which are studied in this report. copia and 297 are 5.0 kb and 7.2 kb in length with about 400 by long terminal repeats (LTRs), respectively (Rubin 1983;Kugimiya et al 1983). Both copia and 297 are copia-like elements which are known to be intimately related in evolution to retroviruses in vertebrates and suggested to transpose via RNA intermediates Saigo et al 1984;Arkcipova et al 1984;Flavell 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have suggested that the eucaryotic transposable elements which are structurally similar to the proviral forms of vertebrate retroviruses might transpose via RNA intermediates (13,14,27,49). A reverse transcription mode of transposition of IAP elements is supported by the fact that all new insertions of these elements have been discovered in IAP-producing cells (for review see reference 16).…”
Section: __________________---_--------------------------------------mentioning
confidence: 99%
“…A major question posed by the observed bidirectional transcription of the solo TED LTR is whether the same (23,38) and copia (9,29), the S. cerevisiae retrotransposon Ty912 (5,8), and the retrovirus human Tlymphotropic virus type III/lymphadenopathy virus (30,39,42,48). …”
Section: Effectsmentioning
confidence: 99%